Perancangan Sistem Informasi Maintenance dan Monitoring Mesin Produksi Berbasiskan Design Thinking Approach pada Perusahaan Busa Poliuretan - Putrika Dewi, Rezayanti Novia (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The rapid development of information technology in Indonesia has driven improvements in efficiency and effectiveness across various industrial sectors, including manufacturing. One of the major challenges frequently encountered in the manufacturing industry is unplanned downtime of production machines, which leads to decreased productivity and increased operational costs. at PT Anugrah Cemerlang Abadi, downtime management is still conducted manually, resulting in the unavailability of timely and accurate information regarding machine conditions. This study aims to design an information system for controlling unplanned downtime based on a Computerized Maintenance Management System (CMMS) to support digital recording, real-time monitoring, and the management of machine and spare parts data. The research adopts the Design Thinking approach proposed consists of five stages: empathize, define, ideate, prototype, and test. System evaluation was conducted using usability testing with the System Usability Scale (SUS) method involving 50 respondents. The results show that the system achieved a SUS score of 89.7, which falls into the Grade A category, is classified as Best Imaginable and Acceptable, and is positioned within the 80th–90th percentile. These findings indicate that the proposed information system demonstrates excellent usability and is suitable for supporting the control of unplanned downtime and enhancing production efficiency within the company.